A leftward bias negatively correlated with performance is selectively displayed by domestic chicks during rule reversal (not acquisition). Issue 1 (4th March 2021) - Loconsole, Maria; Perovic, Sofija; Regolin, Lucia
ABSTRACT: In order to face a constantly changing environment, animals need to be able to update their knowledge of the world on the basis of new information. Often, this means to inhibit a previously acquired response and flexibly change their behaviour to produce a new response. Here, we measured such abilities in young domestic chicks, employing a Colour Reversal Learning Task. During the acquisition phase, 17 one-week-old male chicks had to learn to peck on one of two coloured boxes to obtain a food reward. After reaching criterion, chicks underwent a reversal phase in which the previously learned colour-reward contingency was swapped. As expected from the literature, chicks performed better in the acquisition phase with respect to the reversal phase. Results moreover highlighted the presence of a lateralized bias selectively during reversal: chicks performed better if the stimulus rewarded was located in the left hemispace (processed by the right hemisphere). Interestingly, the bias correlated with the individual difficulty, i.e., it was stronger in those chicks which needed more trials to complete the reversal session. The present study contributes evidence in support of behavioural flexibility in young chicks, along with a novel perspective on lateralized mechanisms that might underlie such ability.